As professoras primárias da Guanabara de Lacerda: a construção do tipo antropológico - Maria Angélica da Gama Cabral Coutinho (EccoS – Revista Científica)
This work intends to comprehend the elementary public education of the old Guanabara State. For this, the text basis on the Cornelius Castoriadis anthropological type theory. This political period corresponds to Carlos Lacerdas government that deeply marked the teachers of this moment.